1986
DOI: 10.1021/ja00285a030
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids chiral at phosphorus. 12. Configurational effect on the thermotropic properties of chiral dipalmitoylthiophosphatidylcholine

Abstract: Differential scanning calorimetry (DSC) studies of the diastereomers of 1,2-dipalmitoyl-sn-glycer0-3-thiophosphocholine (DPPsC) have been carried out to determine the effect of phosphate structure and configuration on the phase-transition properties of these analogues of natural 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) in the multilamellar form. Both the Sp and RP + Sp isomers showed a "pretransition" (Tpt = 43.7 and 43.8 OC, respectively) and a "main transition" ( T , = 45.0 and 44.8 OC, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
5
13
0
Order By: Relevance
“…However, this assumption is not valid for lipids with more than one chiral center, where the 1,2-snand 2,3-sn-glycerol isomers are diastereomers instead of enantiomers. Indeed, the introduction of a second chiral center at phosphorus by replacing an oxygen with a sulfur atom produces diastereomers ofPC that differ significantly in the physical properties of their lamellar phases (23,24). Similar differences in gel-phase polymorphism have also been OR' FIGURE 1 The chemical structure of di-dodecyl-o-D-glucosyl glycerols used in this study.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, this assumption is not valid for lipids with more than one chiral center, where the 1,2-snand 2,3-sn-glycerol isomers are diastereomers instead of enantiomers. Indeed, the introduction of a second chiral center at phosphorus by replacing an oxygen with a sulfur atom produces diastereomers ofPC that differ significantly in the physical properties of their lamellar phases (23,24). Similar differences in gel-phase polymorphism have also been OR' FIGURE 1 The chemical structure of di-dodecyl-o-D-glucosyl glycerols used in this study.…”
Section: Introductionsupporting
confidence: 55%
“…Until recently, it was not known ifthe structures ofthe nonlamellar phases of PEs were dependent on the chirality ofthe glycerol backbone, but the latest measurements of 1,2-sn and racemic dimethyl dihexadecylphosphatidylethanolamine (DHPE) at low water content were unable to detect differences in either the structure or dimensions of the cubic phase formed (27). To date, however, there have been no studies of the physical properties of diastereomeric thio-PEs similar to those of the thio-PCs (23,24). Thus, with glyceroglycolipids, which are known to form both lamellar and nonlamellar structures, the addition of a chiral center at C5 of each sugar molecule might be expected to produce differences in the physical properties of the 1,2-sn and 2,3-sn glycerol isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The isomeric purity was >98% in all cases as judged by 3IP NMR. The samples were repetitively purified by precipitating from acetone/ethanol (10/1) until their DSC traces are identical with those described by Wisner et al (1986).…”
Section: Methodsmentioning
confidence: 99%
“…This stereochemical approach has led us to demonstrate that the phosphate group of phospholipids is involved in the interaction with phospholipase A2 even though it is not directly involved in the reaction (Bruzik et al, 1983;Tsai et al, 1985) and that the same interaction is absent in a functionally related enzyme lecithin-cholesterol acyltransferase (Rosario-Jansen et al, 1990). Applying this approach to the biophysical properties of lipid bilayers, we have shown that the Rp isomer of DPPsC is unusually stable in the subgel phase on the basis of DSC (Wisner et al, 1986), X-ray diffraction, 31P NMR, and FT-IR studies (Sarvis et al, 1988). The FT-IR results also reveal that a key structural feature that could be related to the stable subgel phase of (Rp)-DPPsC is that its C=0 stretching band is asymmetric.…”
mentioning
confidence: 90%
“…It was thereby shown that phospholipase A2 preferentially accepts (R,)-DPP,E as a substrate, whereas phospholipase C accepts (S,)-DPP,E. The chiral thiophospholipids have been used for analysis of the stereochemical course of phosphotransferase action by phospholipase D, as well as for comparative studies of their different properties in various physical states (57)(58)(59).…”
Section: Thiophospholipidsmentioning
confidence: 99%